Analisis Web Performance Load Test Setelah Menggunakan Azure WAF Studi Kasus Pada Aplikasi ERP - Cristianto, Denil; Widiasari, Indrastanti R (Building of Informatics, Technology and Science (BITS), 2022)
The increasing use of web applications is certainly proportional to the increase in cybersecurity attacks that occur. Many companies or agencies are less concerned about the security of the web applications that are used so that these web applications can be easily hacked. On the other hand, there are many ways to protect websites from hacker attacks, one of which is implementing waf. WAF is an application or device that has the ability to filter, monitor, and block traffic that goes to a website. The waf used in this study is a cloud-based waf, namely azure application gateway. Based on this, this study aims to discuss web performance analysis and load testing of a website after implementing waf. The tools used to test Web Performance and Load Test are GTMetrix and Pingdom Tools. With this research, it is hoped that this research can be a reference for individuals or agencies that will implement waf